An investigation on Moringa oleifera fruit (drumstick)‐derived cellulose micro and nanofiber reinforced styrene butadiene rubber composites. Issue 5 (25th February 2023) - Koley, Riya; Ghorai, Uttam Kumar; Chattopadhyay, Santanu; Bhowmick, Anil K.
Abstract: The current focus in the elastomer industry is to look for biobased or natural filler for various compounds. The reinforcing effect of waste drumstick‐derived cellulose micro and nanofiber in styrene butadiene rubber (SBR) was investigated for the very first time. Cellulose microfibers and nanofibers were isolated from the drumstick fruit peel and characterized using different techniques such as x‐ray diffraction, scanning and transmission electron microscopy, and x‐ray photoelectron spectroscopy. The filler‐polymer interaction in the composites was studied using the bound rubber measurements, which showed that the bound rubber content of the composite increased from 0.5% to 8.1% at 5 phr cellulose nanofiber loading. The tensile strength and modulus of the modified cellulose microfiber‐containing composite were higher than both the unfilled SBR and the raw fiber‐SBR composites. The addition of 5 phr nanofiber to SBR showed a 46% increment of the tensile strength than the control compound. The die swell index of the cellulose fiber reinforced composites came down attesting the better processability of the extrudates. The addition of cellulose fiber also improved the wet skid resistance of the composites as seen from dynamic mechanical thermal analysis. Hence, this work confirms the application of modified drumstick microfibers and nanofibers as sustainable fillers for high‐performance elastomers composites. Abstract : For the first time, Moringa oleifera fruit (drumstick) derived cellulose micro and nanofibers were used for the reinforcement of nonpolar styrene butadiene rubber.